2014
DOI: 10.1016/j.bbrc.2014.02.089
|View full text |Cite
|
Sign up to set email alerts
|

Defective adipose tissue development associated with hepatomegaly in cathepsin E-deficient mice fed a high-fat diet

Abstract: Running title: Fat-induced cathepsin E-deficient mice Key words: cathepsin E, high-fat diet, adipose tissue AbstractCathepsin E is an intracellular aspartic proteinase, which is predominantly distributed in immune-related and epithelial cells. However, the role of the enzyme in adipose tissues remains unknown. In this study, we investigated the characteristics of cathepsin E-deficient (CatE -/-) mice fed a high-fat diet (HFD), as a mouse model of obesity. HFD-fed CatE -/-mice displayed reduced body weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Ctse is an intracellular aspartic proteinase highly expressed in immune-related cells such as macrophages. Its main role is in macrophage infiltration, adipogenesis, and hepatic steatosis [54]. Orm2 is expressed in hepatocytes and adipocytes and secreted into plasma under metabolic and inflammatory stress as an acute phase reactant immunomodulator protein [55].…”
Section: Discussionmentioning
confidence: 99%
“…Ctse is an intracellular aspartic proteinase highly expressed in immune-related cells such as macrophages. Its main role is in macrophage infiltration, adipogenesis, and hepatic steatosis [54]. Orm2 is expressed in hepatocytes and adipocytes and secreted into plasma under metabolic and inflammatory stress as an acute phase reactant immunomodulator protein [55].…”
Section: Discussionmentioning
confidence: 99%
“…Cfhr1 is upregulated in the mouse retina in response to a different high fat diet (Z heng et al 2015). Ctse deficient mice fed a high fat diet showed hypercholesterolemia, reduced body weight gain and impaired fat development compared to controls mice (K adowaki et al 2014). F13b is part of the coagulation cascade and has not been previously associated with cholesterol metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Adipose tissue and liver are the most important organs which control lipid metabolism in our body and impaired adipogenesis have been linked to liver lipogenesis in some studies [9][10][11][12][13]. Diraison et al [9] found increased hepatic lipogenesis but decreased expression of lipogenic gene in adipose tissue in obese patients.…”
Section: Discussionmentioning
confidence: 97%
“…ACCEPTED MANUSCRIPT 11 as, hepatic lipid deposition, diabetes and cardiovascular disease [11][12][13]. A large number of studies have confirmed that chronic inflammation is closely related to both adipogenesis and hepatic lipogenesis [14][15][16].…”
Section: Accepted Manuscriptmentioning
confidence: 93%